2007
DOI: 10.2471/blt.06.031047
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the community impact of lymphatic filariasis: a review of the sociocultural literature

Abstract: Lymphatic filariasis (LF) is endemic in approximately 80 tropical and subtropical countries. About 120 million people are infected with the parasite and a billion are estimated to be at risk of infection. The main focus of the LF elimination programme to date has been to interrupt transmission by means of annual community-wide treatment campaigns with diethylcarbamazine and albendazole, or albendazole and ivermectin, for a period of four to six years. Although substantial progress has been recorded wherever th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
1
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(95 citation statements)
references
References 29 publications
(40 reference statements)
1
81
1
6
Order By: Relevance
“…Ayrıca WHO' ya göre, LF akıl hastalığından sonra uzun süreli engelliliğin en sık görülen ikinci nedeni olarak belirtilmiştir (30 Gıda kaynaklı trematod enfeksiyonları ile dünya genelinde 40 milyondan fazla kişi enfekte olup dünya nüfusunun %10'undan fazlası risk altındadır. Önceki yıllarda geleneksel olarak sınırlı bölgelerde ve özellikle gelir düzeyi düşük toplumlarda görülen gıda kaynaklı trematod enfeksiyonları, şuanda büyüyen uluslararası piyasalar ve ulaşım sistemlerinin geliştirilmesi ile daha geniş dağılım alanı göster-mektedir (36).…”
Section: Lenfatik Filariasisunclassified
“…Ayrıca WHO' ya göre, LF akıl hastalığından sonra uzun süreli engelliliğin en sık görülen ikinci nedeni olarak belirtilmiştir (30 Gıda kaynaklı trematod enfeksiyonları ile dünya genelinde 40 milyondan fazla kişi enfekte olup dünya nüfusunun %10'undan fazlası risk altındadır. Önceki yıllarda geleneksel olarak sınırlı bölgelerde ve özellikle gelir düzeyi düşük toplumlarda görülen gıda kaynaklı trematod enfeksiyonları, şuanda büyüyen uluslararası piyasalar ve ulaşım sistemlerinin geliştirilmesi ile daha geniş dağılım alanı göster-mektedir (36).…”
Section: Lenfatik Filariasisunclassified
“…Worldwide, the main cause of lymphedema is Wlariasis, in over 80 tropical and subtropical countries, with about 120 million people aVected (Wynd et al 2007). This disease is caused by infection with the mosquito-borne parasites Wuchereria bancrofti and Brugia malayi, which live and reproduce in the lymphatic system.…”
Section: Pathology Of Lymphatic Vesselsmentioning
confidence: 99%
“…Gyapong et al [14] found that hydroceles had a significant impact on young men, particularly at a time when they were struggling to establish their sexual identity and their capacity to be reliable economic providers. However, unwillingness of men to admit to sexual dysfunction may shroud the real extent of this issue [11].…”
Section: The Social Impact Of Disease On Individuals and Productivitymentioning
confidence: 99%
“…Filarial hydroceles can have significant, and often negative, social impacts [7,[9][10][11]. The degree of social disability varies among cultural settings, but the extent of stigmatization appears to be directly correlated with the severity of visible disease [12,13].…”
Section: The Social Impact Of Disease On Individuals and Productivitymentioning
confidence: 99%